SINGULAR THERAPEUTIC PROJECT FOR PROFESSIONALS IN THE FAMILY HEALTH STRATEGY - Ariná Islaine da Silva; Maria Fernanda Lehmkuhl Loccioni; Renata Fabricia Orlandini; Jeferson Rodrigues; Girlane Mayara Peres; Mariluci Alves Maftum (Universidade Federal do Paraná, 2016)
The objective was to analyze the importance of the Singular Therapeutic Project in care management for professionals from a Family Health Strategy team in the context of Primary Health Care in a state capital in the South of Brazil. The Singular Therapeutic Project is a problem-solving device in cases of important vulnerability because it organizes the work process and permits care based on the expanded clinic, respecting the subject's singularity. A qualitative and descriptive study was undertaken by means of semistructured interviews with five professionals between August and September 2014. The results show two categories: the identification and establishment of the Project for the families with longitudinal care needs; the limits and challenges in the implementation of the Project in Primary Health Care. In conclusion, there are limits, such as the inclusion of the Singular Therapeutic Project in the information system; as well as challenges, such as indicators for its assessment by the Family Health Strategy team.